2019
DOI: 10.1158/1535-7163.mct-17-1234
|View full text |Cite
|
Sign up to set email alerts
|

A Kinase Inhibitor with Anti-Pim Kinase Activity is a Potent and Selective Cytotoxic Agent Toward Acute Myeloid Leukemia

Abstract: More than 40 years ago, the present standard induction therapy for acute myeloid leukemia (AML) was developed. This consists of the metabolic inhibitor cytarabine (AraC) and the cytostatic topoisomerase 2 inhibitor daunorubucin (DNR). In light of the high chance for relapse, as well as the large heterogeneity, novel therapies are needed to improve patient outcome. We have tested the anti-AML activity of 15 novel compounds based on the scaffolds pyrrolo [2,3-a]carbazole-3-carbaldehyde, pyrazolo[3,4-c]carbazole,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…PIM kinases promote NF-κB constitutive activation and at the same time it is regulated by NF-κB. Several PIM kinase inhibitors, such as AZD1208, SMI-4a, SGI-1776, YPC-21440 and YPC-21817, have been shown to inhibit the growth of AML cells in vitro and in vivo [ 86 , 88 , 175 , 176 ]. The most advanced PIM1 inhibitor, SEL24/MEN1703, which inhibits both PIM1 and FLT3, is currently in clinical trial for AML patients.…”
Section: Inhibitors Of Upstream Regulators Of Nf-κbmentioning
confidence: 99%
“…PIM kinases promote NF-κB constitutive activation and at the same time it is regulated by NF-κB. Several PIM kinase inhibitors, such as AZD1208, SMI-4a, SGI-1776, YPC-21440 and YPC-21817, have been shown to inhibit the growth of AML cells in vitro and in vivo [ 86 , 88 , 175 , 176 ]. The most advanced PIM1 inhibitor, SEL24/MEN1703, which inhibits both PIM1 and FLT3, is currently in clinical trial for AML patients.…”
Section: Inhibitors Of Upstream Regulators Of Nf-κbmentioning
confidence: 99%
“…Compounds 20 and 21 substituted at the 1-position showed improved Pim-1 inhibitory potency and induced apoptosis in AML MOLM-13 cells, however without reaching a cytotoxicity as potent as that of VS-II-173. This could be due to the efficient targeting by VS-II-173 of other cellular targets (VS-II-173 is a multi-kinase inhibitor 5 ) and/or to a different 10 cellular distribution of 20/21 within the cellular compartments due to their higher lipophilicity (20 and 21 cLopP = 1.99 and 2.21, 15 respectively, instead of 1.46 for VS-II-173). In addition, compound 20 and 21 showed low cytoxicity toward non-cancerous NRK cells.…”
Section: Scheme 2 Synthesis Of Compounds 20 and 21mentioning
confidence: 99%
“…4 Derivatives substituted at the 5-, 8-, 9-and 10-positions were synthesized 4 and compound VS-II-173 was identified as a potent and selective cytotoxic agent toward AML patient blasts including some carrying mutations associated with poor diagnosis (Figure 1). 5 Importantly, it was demonstrated that substitution at the 5-position by a nitro group was crucial for potent Pim inhibition. Moreover, molecular modelling studies showed that the nitro group of VS-II-173 could be involved in hydrogen bonding with the ATP binding site of Pim.…”
mentioning
confidence: 99%
“…Currently, inhibitors are tested for many protein kinases, including PIM serine-threonine kinases 1, 2 and 3. PIM kinases are overexpressed in AML and solid tumors such as colon cancer or prostate tumor, which is associated with poor prognosis [221][222][223]. Pan-Pim kinase inhibitors from the imidazopyridazine-thiazolidinediones group have been shown to exert anti-neoplastic activity in various neoplastic types in vitro and in vivo [224].…”
Section: The Progress Of Targeted Therapymentioning
confidence: 99%